Resale price maintenance in South African competition law - Spangler, Simon (School For Advanced Legal Studies, 2026)
Resale Price Maintenance (‘RPM') refers to a particular type of vertical agreement in which an upstream firm controls or restricts the price at which a downstream firm can on-sell its product or service, typically to final consumers.1 Usually the parties agree to set either a minimum or maximum resale price. Maximum RPM covers those situations in which an upper limit or ceiling is placed on the price the retailer can charge for a product. In contrast, when it comes to minimum RPM, a lower bound or floor is placed on the price at which the retailer can on-sell the product.2 Fixing the minimum resale price is generally treated more strictly by competition law as it is considered to have more severe anti-competitive effects, for example the elimination or reduction of intra-brand competition and an increase in price transparency that might facilitate horizontal collusion upstream or downstream.